Teaching Hinduism For The Blinds: A Study On Hinduism Teaching And Learning In SLB A Negeri Denpasar - I Gusti Ngurah Agung Wijaya Mahardika (Institut Hindu Dharma Negeri Denpasar, 2017)
This paper focuses on the study conducted in SLB A Negeri Denpasar. The aim of the study was to identify the model of teaching used in teaching Hinduism to blind students in SLB A Negeri Denpasar. The study was conducted to the A program of SLB A Negeri Denpasar. The data were collected through observation, interview and document study. The result of the study showed that the teaching model used in teaching Hinduism was different than the teaching model used in normal school, viewed from the aspects of Syntax, Social System, Principle of Reaction, Support System, and instructional and nurturant effects of the model. The teaching model used was found to be a mix between the Direct Instruction Model and the Nondirective Teaching Model.